Skype me! from single user to small enterprise and beyond - Gough, Michael, 1963- (Rockland, Mass. : Syngress, 2006)
This book is divided into four parts. Part I begins with several chapters on the basics of Skype. Here the reader learns how to install and configure Skype on several platforms including Windows, Max OSX, Linux, and PocketPC. The reader will also learn how to begin making voice over IP calls immediately. Part II deals with the more advanced features of Skype. Here the reader learns how to use Skype on new Skype Ready cell phones, use Skype for more advanced, business-oriented tasks such as scheduling and file transfers, as well as using SkypeOut. Part III discusses how to integrate Skype with third party networking, communication, and security devices such as routers, firewalls, and mail servers, as well as using the brand new Skype for Business. Part IV covers the Skype Application Programming Interface, Plug-ins, Add-ons, and third party tools. Here the reader learns to develop and customize their own applications using the new, powerful, Skype API. * Skype has over 70,000,0000 users worldwide, and 13 forums with over 25,000 members * Skype's Application Programming Interface (API) allows users to develop their own applications and customize Skype with the information found in this book * Makrus Daehne is one of the most recognized and respected authorities on Skype and he is the forum moderator on the Skype Web site.
PART 1: SKYPE BASICS -- 1. What is Skype? -- 2: Installing (Windows, MacOS, Linux, PocketPC) -- 3: Configuration (Windows, MacOS, Linux, PocketPC) -- 4: Usage PART II: SKYPE FOR ADVACED USERS -- 5: Manual Configuration -- 6: Special Settings -- 7: Technical Background -- 8: Future Development -- 9: Skype goes Mobile Part III: Additional Hardware 10: Hardware Overview -- 11: General (Primary) Hardware -- 12: External Hardware -- 13: Hardware Systems and Converters -- 14: Special Hardware Drivers PART IV: PLUGINS, ADDONS AND 3rd PARTY TOOLS -- 15: Overview -- 16: Answering Machine -- 17: Camera Add-on -- 18: Whiteboard Tools -- 19: Messenger Integration -- 20: Outlook Integration Appendixes: ERROR DATABASE 21: Error Codes -- 22: Error FAQ -- 23: General Problems with Networks.
Includes index.
Keywords: Skype (Electronic resource); Internet telephony; Internetworking (Telecommunication); Electronic books